Relationship Between Work Duration and Work Process with Low Back Pain Among Coffee Farmers - Ulfa Husna Dhirah; Hasratina, Illa (Madago Nursing Journal, 2025)
Background: Low back pain (LBP) is a major occupational health concern among agricultural workers, yet evidence specific to smallholder coffee farmers regarding the combined impact of work duration and work processes remains limited, particularly in the context of developing economies like Indonesia. Methods: An analytical cross-sectional study was conducted from 1–13 October 2025 in Tunyang Induk Village, Indonesia. Using total population sampling, 135 coffee farmers participated. Data were collected through face-to-face interviews using a structured questionnaire that assessed sociodemographic variables, work duration (categorized as ≤8 hours or >8 hours/day), work processes (evaluated using an adapted Quick Exposure Check tool and categorized as "good" or "poor"), and low back pain (assessed via the Nordic Musculoskeletal Questionnaire). Data analysis involved descriptive statistics, chi-square tests, and logistic regression using SPSS version 26.0, with statistical significance set at p < 0.05. Results: The prevalence of low back pain among coffee farmers was 65.2% (n=88). Of those with LBP, 59.1% reported moderate-to-severe pain, and 72.7% indicated that pain interfered with daily farming activities. Bivariate analysis revealed strong associations between LBP and both extended work duration (>8 hours/day; OR = 33.1, 95% CI: 12.8–85.6, p < 0.001) and poor work processes (OR = 215.8, 95% CI: 56.2–828.9, p < 0.001). Significant associations were also found with age ≥40 years (OR = 2.2, p = 0.027) and farming experience ≥10 years (OR = 2.5, p = 0.011). Conclusion: Prolonged work hours and inadequate ergonomic practices are significant, independent risk factors for low back pain among Indonesian coffee farmers. These findings highlight an urgent need for ergonomic interventions, structured work-rest scheduling, and community-based health education programs to reduce musculoskeletal strain. Future efforts should integrate occupational health perspectives into agricultural policy and expand the role of community nursing in preventive ergonomic care.